1959
DOI: 10.1037/h0048093
|View full text |Cite
|
Sign up to set email alerts
|

Relations between the behavioral syndrome produced by lesions in the septal region of the forebrain and maze learning of the rat.

Abstract: Lesions in the septal region of the forebrain oftein produce a state of hyperirrilability in rats characterized chiefly by an exaggerated startle response lo tactile stimuli applied to the animal's back and intense and aggressive resistance to handling (Brad}' & Nauta, 1953). These behavioral manifestations (septal syndrome) tend to abate over a period of weeks (Brady & Nauta, 1955). The specific ncuroanatomic structures which must be destroyed to produce the septal syndrome have not been clearly specified (Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
2
1

Year Published

1962
1962
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 9 publications
0
28
2
1
Order By: Relevance
“…They would also run back and forth in the same alley in an agitated manner. Anologous observations were reported in the rats with septal lesions (Thomas, et al, 1959). Such agitated exploratory behavior of the hippocampus-ablated animals may account for their tendency to make more errors.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…They would also run back and forth in the same alley in an agitated manner. Anologous observations were reported in the rats with septal lesions (Thomas, et al, 1959). Such agitated exploratory behavior of the hippocampus-ablated animals may account for their tendency to make more errors.…”
Section: Discussionmentioning
confidence: 83%
“…Several other studies indicate that the hyperactivity is often produced in animals which are subjected to bilateral ablation of the brain, e.g., the frontal area of the cortex (Kennard et al, 1941;Ruch et al, 1943), the caudate nucleus (Davis, 1958), the anterior hypothalamus (Maire & Patton, 1954), the septal region (Thomas et al, 1959), the amygdaloid nucleus (Schwartzbaum et al, 1961), and the hippocampus (Kim, 1960). In view of these findings, the question arises as to whether these brain structures are equipotential with regard to general activity.…”
Section: Discussionmentioning
confidence: 99%
“…Dickinson (1973) found that if a successive go/no-go discrimination, in which septal damage had been shown to produce persistence , was converted into a succ~ssivg o/go discjimi na ti o n with the same st~muh and reinforcement schedules, operated anunals performed at least as efficiently as controls. Perhaps t~e strongest evidence that septal damage does not result m any general learning deficit comes from the similarity of acquisition functions of septal and intact rats in a variety of complex mazes (Thomas , Moore, Harvey, & Hunt, 1959;Ain, Lubar , Moon, & Kulig, 1969) although it should be noted that a deficit in a complex reasoning task has been reported (Stahl & Ellen, 1973). Finally in the rat, at least, septal lesions produce little detectable change in a range of species-specific behavior (Slotnick, 1967;Lubar, Herrman, Moore, & Shouse, 1973) .…”
Section: Selectivity Of Dysfunctionsmentioning
confidence: 99%
“…In a series of experimental studies, spanning over 4 decades, Thomas dissected the contribution of anatomical areas and pathways, including the precommissural fornix, septal region, septohippocampal circuitry, mediodorsal thalamus, and prelimbic cortex, to short-term spatial memory, by evaluating the effect of stereotaxic lesions with tests of reinforced alternation in a T-maze [17,18,19,20,21,22]. …”
Section: Figmentioning
confidence: 99%